PLAGIARISME ABSTRAK MENGGUNAKAN ALGORITMA WINNOWING DAN SYNSETS - Julius Evan Harya Chandra; Viny Christanti M; Dali S Naga (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Plagiarism checker is a tool or media that useful to detect whether a document is a plagiarism or not. In most cases, plagiarism checker system only detect plagiarism between 2 documents tested. This would be a problem if you want to detect multiple documents at once. Abstract Plagiarism checker is designed to have ”one to one” feature that is checking only between 2 abstract documents and other feature is ”one to many” that is  checking multiple abstract documents at once.This Plagiarism checker is used Winnowing algorithm to used to check the similarity of words in the document. For the result of the percentage of similarity between 2 documents, the system are used 2 methods that is Dice similarity and Jaccard similarity. The test result performed to determine the value of k-gram, base and window that are used in Winnowing algorithm. For the testing of the k-gram, base and window values,the results are 8, 13 and 6.In the system calculation test, the Jaccard method is closer to the real value by 5%. In the evaluation test, the abstract data used are 9 abstracts with Game interest. The 9 abstracts are obtained precision value 1, recall value 1, and the accuracy is 100%.